Structural, optical and magnetic behavior of (Pr, Fe) co-doped ZnO based dilute magnetic semiconducting nanocrystals. Issue 14 (15th July 2022) - Kabir, Fazal; Murtaza, Adil; Saeed, Azhar; Ghani, Awais; Ali, Anwar; Khan, Saleh; Li, Kaili; Zhao, Qizhong; Yao, Kang Kang; Zhang, Yin; Yang, Sen
Abstract: The development of ZnO-based dilute magnetic semiconductor nanostructures co-doped with rare-earth and transition metals has attracted substantial attention for spintronics application. In this work, Pr (1%) and Fe (1%, 3%, and 5%) co-doped ZnO nanoparticles (NPs) were synthesized via co-precipitation method, and their structural, morphological, optical, photoluminescence, and magnetic properties were investigated. The single-phase wurtzite hexagonal crystal structure of all samples was detected via X-ray diffraction. Morphological analysis revealed spherical shape of the NPs with an average size in 20–50 nm range. The ultraviolet (UV)–visible measurements showed a redshift in the UV band and a slight change in the bandgap of the co-doped NPs. Fourier transform infrared analysis proved the existence of different functional groups in all synthesized NPs. X-ray photoelectron spectroscopy confirmed that Pr and Fe ions incorporated in the host ZnO lattice exhibit Pr 3+ and Fe 3+ oxidation states, respectively. Photoluminescence analysis showed that incorporated ions induce characteristic emission bands and structural defects in the synthesized NPs. Magnetic characterization indicated that the ZnO NPs exhibit a diamagnetic nature. However, the (Pr, Fe) co-doped NPs exhibit ferromagnetism at room temperature because of the interactions between Pr 3+ and Fe 3+ ions and trapped electrons mediated by bound magnetic polarons. Excellent optical and magnetic properties of synthesized samples may render them promising candidates for spintronics applications.